Deforestación y regeneración de bosques en resguardos recientemente ampliados en la región del Medio Río Caquetá (2022)
This work quantifies the areas of forest cover loss from 2001 to 2021 and forest cover gain between 2000 and 2012 in three recently expanded indigenous reservations in the middle Caquetá River region: Puerto Zábalo- Los Monos (PZLM), Monochoa and Aduche. It, aims for an approximation to whether the constitution of Indigenous Reservations’ collective property contributes to the reduction of deforestation. The deforested and reforested areas were quantified both on the original reservations (before being expanded) as well as in the expanded zones, based on the open access information from Global Forest Change (Hansen et al., 2013). On the PZLM and Monochoa’s reservations, there was evidence of reduced deforestation in the years immediately after their expansions (2017 and 2018). Meanwhile, in the case of the Aduche reservation, an increase was observed.